Principle of direct van der Waals epitaxy of single-crystalline films on epitaxial graphene - Kim, Jeehwan; Bayram, Can; Park, Hongsik; Cheng, Cheng-Wei; Dimitrakopoulos, Christos; Ott, John A.; Reuter, Kathleen B.; Bedell, Stephen W.; Sadana, Devendra K. (Nature communications, 2014)
There are numerous studies on the growth of planar films on sp 2 -bonded two-dimensional (2D) layered materials. However, it has been challenging to grow single-crystalline films on 2D materials due to the extremely low surface energy. Recently, buffer-assisted growth of crystalline films on 2D layered materials has been introduced, but the crystalline quality is not comparable with the films grown on sp 3 -bonded three-dimensional materials. Here we demonstrate direct van der Waals epitaxy of high-quality single-crystalline GaN films on epitaxial graphene with low defectivity and surface roughness comparable with that grown on conventional SiC or sapphire substrates. The GaN film is released and transferred onto arbitrary substrates. The post-released graphene/SiC substrate is reused for multiple growth and transfer cycles of GaN films. We demonstrate fully functional blue light-emitting diodes (LEDs) by growing LED stacks on reused graphene/SiC substrates followed by transfer onto plastic tapes. Large-scale growth of single crystals on graphene can be useful for the development of 3D/2D or 2D/2D heterostructures. Here, through careful control of growth kinetics, the authors perform multiple cycles of direct growth/transfer of high-quality single-crystal GaN, using a single graphene/SiC substrate.